2010
DOI: 10.1037/a0021703
|View full text |Cite
|
Sign up to set email alerts
|

Substance use among Asian American adolescents: Influence of race, ethnicity, and acculturation in the context of key risk and protective factors.

Abstract: This study examines the relative influence of race/ethnicity, acculturation, peer substance use, and academic achievement on adolescent substance use among different Asian American ethnic groups and U.S. racial/ethnic groups. Data from the Wave 1 in-home sample of the National Longitudinal Study of Adolescent Health was used to examine lifetime use of alcohol, tobacco, and marijuana in a full adolescent sample of all racial/ethnic groups (N=20,745) and a subsample of Asian American adolescents (N=1,248). Path … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 66 publications
4
44
1
Order By: Relevance
“…Our multivariate analyses corroborate results of previous research (e.g., Hussey et al, 2007;Thai et al, 2010) that firstgeneration of Asian American adolescents tend to consume less alcohol and recreational drugs than their native coethnics (third plus generation). However, no generational differences were shown on tobacco use.…”
Section: Discussionsupporting
confidence: 90%
“…Our multivariate analyses corroborate results of previous research (e.g., Hussey et al, 2007;Thai et al, 2010) that firstgeneration of Asian American adolescents tend to consume less alcohol and recreational drugs than their native coethnics (third plus generation). However, no generational differences were shown on tobacco use.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, whereas researchers generally find that higher academic achievement is associated with reduced alcohol use (Kostelecky, 2005), tobacco use (Scal, Ireland, & Borowsky, 2003), and general substance use (Thai, Connell, & Tebes, 2010), this is not always the case (Fang, Barnes-Ceeny, & Schinke, 2011;Meyers, 2013). Similarly, research generally supports the notion that self-esteem and self-efficacy are protective against suicidal ideation (Babiss & Gangwisch, 2009;Kidd & Shahar, 2008;Sharaf, Thompson, & Walsh, 2009); however, Roberts, Roberts, and Xing (2010) failed to find this association.…”
Section: Factors Protecting Adolescents From Risk Behaviors and Emotimentioning
confidence: 76%
“…In particular, prior findings indicate that greater experiences with acculturation related pressures (e.g., discrimination, social norms, language competencies) may be associated with higher levels of risky behavior engagement (e.g., alcohol and substance abuse, aggression, rule breaking) among immigrant minority adolescents and young adults (e.g., Latino, Asian; Forster et al, 2015; Gil et al, 2000; Kam, 2011; Thai, Connell, & Tebes, 2010). In a study with recently immigrated Hispanic youth, researchers found that higher levels of acculturation-related stress (e.g., embarrassment about having an accent or not speaking English well) were positively associated with deviant behaviors (i.e., aggression, rule breaking behavior; Forster et al, 2015).…”
Section: Acculturative Stress and Young Mexican-origin Mothers’ Admentioning
confidence: 99%